2018
DOI: 10.1111/iej.12905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bioactivity of fluoride‐enriched mineral trioxide aggregate on osteoblasts

Abstract: The addition of fluoride modulated the biocompatibility of MTA in terms of supporting bone cell proliferation and hard tissue formation. Hence, fluoride enrichment is a trend-setting advancement for MTA-based endodontic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Biomineralization is the process by which a living organism synthesizes mineral substance. One important challenge facing endodontics today is precisely the correct formation of hard mineral tissue . To achieve this, it is essential that the materials used in endodontic treatments be bioactive.…”
Section: Discussionmentioning
confidence: 99%
“…Biomineralization is the process by which a living organism synthesizes mineral substance. One important challenge facing endodontics today is precisely the correct formation of hard mineral tissue . To achieve this, it is essential that the materials used in endodontic treatments be bioactive.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts. Proksch et al (156) found that MTA impairs proliferation, osteogenic differentiation and extracellular matrix mineralization of primary human osteoblasts derived from the alveolar bone; this could be restored by addition of fluoride to MTA. Similarly, MTA inhibits proliferation and COL1 gene expression in bone marrow osteoblasts from rat femur (157).…”
Section: Osteoblasts/osteoclastsmentioning
confidence: 99%
“…Moreover, bacterial biofilms may also cause persistent intraradicular and extraradicular infection leading to the destruction of periapical bone tissue (Chrepa et al, 2017). In the recent years, research are focused on promoting the regeneration of periapical bone tissue in refractory apical periodontitis therapies (Gjoksi et al, 2017; Proksch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%